Dynamic Governance in Indonesia’s Education Allocation Policy - Arma, Nur Ambia (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2025)
This study aims to examine the development of research on the topic of "Dynamic Governance Public Finance" and possible research plans based on journals published on the topic. The approach used is exploratory qualitative with two stages of analysis: bibliometric analysis and contextual analysis of the school operational assistance (BOS) fund policy in Indonesia. The bibliometric analysis was conducted on 340 scientific articles on the theme of Dynamic Governance and Public Finance indexed in the Dimensions database using Vosviewer software. The mapping results identified six main clusters: fiscal transparency, program efficiency, education governance, university collaboration, market dynamics, and issues of economic growth and social inequality. This pattern suggests that global research continues to focus on efficiency and accountability, while the adaptive and collaborative dimensions of fiscal governance remain relatively underdeveloped. A contextual analysis was then conducted on the BOS fund policy in Indonesia as an empirical illustration of the application of dynamic governance principles in public finance. The results indicate that reforms in fund distribution capacity mechanisms, digitalization of reporting, and cross-ministerial coordination reflect the government's adaptive, reflective, and collaborative capacity. This research emphasizes the importance of developing a dynamic fiscal governance paradigm as a conceptual framework for understanding adaptive, innovative, and sustainable public financial governance.